Hepatitis C outbreak in a respiratory care ward associated with frequent injections: Taiwan, 2017 - Wu, Pei-Yuan; Hung, Min-Nan; Huang, Wei-Lun; Yang, Jyh-Yuan; Su, Chia-ping (Journal of microbiology, immunology and infection, 2021)
Healthcare-associated outbreaks of hepatitis C virus (HCV) infection pose serious risks of harm to patients. During May–July 2017, the Taiwan Centers for Disease Control were notified of four patients with acute HCV infection in a respiratory care ward (RCW). To prevent further infection, an investigation was conducted to identify the transmission route and risk factors for infection. We tested patients and staff members of the RCW for HCV, reviewed medical records, observed infection control practices on-site, and undertook a case–control study. We defined cases as individuals who had stayed in the RCW 2 weeks to 6 months prior to the laboratory diagnosis date of the first case and were infected with HCV after admission. Patients who were hospitalized during the same period but whose HCV tests were negative were selected as controls. We used Mann–Whitney U test to compare the frequency of injections among cases and controls. Of 19 staff and 29 patients, we identified four case-patients and one patient with chronic hepatitis C whose HCV RNA similarity was >98%. Compared to the 12 controls, the case-patients received more injections per day (4.4 vs. 0.1; p = 0.01). The RCW lacked designated areas and standardized workflows for injection preparation. Disinfection of the environment and equipment was inadequate, which could possibly lead to blood contamination of the environment and parenteral medications. HCV infection was associated with frequent injections and infection control lapses. Healthcare workers should follow safe injection practices and reduce injection frequency to prevent HCV transmission.